Fundamental study on quality assurance (QA) procedures for a real‐time tumor tracking radiotherapy (RTRT) system from the viewpoint of imaging devices. Issue 7 (2nd June 2021) - Kimura, Suguru; Miyamoto, Naoki; Sutherland, Kenneth L.; Suzuki, Ryusuke; Shirato, Hiroki; Ishikawa, Masayori
Abstract: Purpose: The real‐time tumor tracking radiotherapy (RTRT) system requires periodic quality assurance (QA) and quality control. The goal of this study is to propose QA procedures from the viewpoint of imaging devices in the RTRT system. Methods: Tracking by the RTRT system (equips two sets of colored image intensifiers (colored I.I.s) fluoroscopy units) for the moving gold‐marker (diameter 2.0 mm) in a rotating phantom were performed under various X‐ray conditions. To analyze the relationship between fluoroscopic image quality and precision of gold marker coordinate calculation, the standard deviation of the 3D coordinate (σ3D [mm]) of the gold marker, the mean of the pattern recognition score (PRS) and the standard deviation of the distance between rays (DBR) (σDBR [mm]) were evaluated. Results: When tracking with speed of 10‐60 mm/s, σDBR increased, though the mean PRS did not change significantly (p>0.05). On the contrary, the mean PRS increased depending on the integral noise equivalent quanta (∫NEQ) that is an indicator of image quality calculated from the modulation transfer function (MTF) as an indicator of spatial resolution and the noise power spectrum (NPS) as an indicator of noise characteristic. Conclusion: The indicators of NEQ, MTF, and NPS were useful for managing the tracking accuracy of the RTRT system. We propose observing the change of these indicators as additional QA procedures for each imaging device from the commissioning baseline.